The Ombudsman and Access to Justice in the Financial Sector from an Islamic Perspective - Damar Sugeng Utomo (Jurnal El-Thawalib, 2026)
Access to justice for consumers in the financial sector is crucial. Beyond simply resolving problems, access to justice emphasizes that the government and authorized institutions should not act arbitrarily. In Islamic civilization, a concept known as Wilayatul Mazhalim has similar meaning to the Ombudsman. Furthermore, history explains that the establishment of the first Ombudsman in Sweden was inspired by the rapidly developing Islamic civilization in Turkey at that time. This is normative juridical research with a qualitative approach, resulting in recommendations for changing the wording of regulations. Primary data were obtained from observation by the researchers during 2022 to 2024, and secondary data sources included laws, presidential decrees, and Financial Service Authority regulations. The data collection techniques were observation and documentation studies. The analysis was conducted narratively by providing definitions in advance. As a result, the Ombudsman that is unable to examine institutions entrusted with dispute resolution transfers on the grounds that such institutions do not receive funding from the State Budget (APBN) or Regional Budgets (APBD) creates an entry barrier and limits access to justice. Such situation differs from the Islamic perspective, which recognizes the rights of individuals to seek and obtain their right without obstruction.